Applying cognitive task analysis to health services research. (9th December 2022) - Graham, Laura A.; Gray, Caroline; Wagner, Todd H.; Illarmo, Samantha; Hawn, Mary T.; Wren, Sherry M.; Iannuzzi, James; Harris, Alex H. S.
Abstract: Objective: Designing practical decision support tools and other health care technology in health services research relies on a clear understanding of the cognitive processes that underlie the use of these tools. Unfortunately, methods to explore cognitive processes are rarely used in health services research. Thus, the objective of this manuscript is to introduce cognitive task analysis (CTA), a family of methods to study cognitive processes involved in completing a task, to a health services research audience. This methods article describes CTA procedures, proposes a framework for their use in health services research studies, and provides an example of its application in a pilot study. Data Sources and Study Setting: Observations and interviews of health care providers involved in discharge planning at six hospitals in the Veterans Health Administration. Study Design: Qualitative study of discharge planning using CTA. Data Collection/Extraction Methods: Data were collected from structured observations and semi‐structured interviews using the Critical Decision Method and analyzed using thematic analysis. Principal Findings: We developed an adaptation of CTA that could be used in a clinical environment to describe clinical decision‐making and other cognitive processes. The adapted CTA framework guides the user through four steps: (1) Planning, (2) Environmental Analysis, (3) Knowledge Elicitation, and (4) Analyses and Results. This adapted CTA framework provides an iterative and systematic approach to identifying and describing the knowledge, expertise, thought processes, procedures, actors, goals, and mental strategies that underlie completing a clinical task. Conclusions: A better understanding of the cognitive processes that underly clinical tasks is key to developing health care technology and decision‐support tools that will have a meaningful impact on processes of care and patient outcomes. Our adapted framework offers a more rigorous and detailed method for identifying task‐related cognitive processes in implementation studies and quality improvement. Our adaptation of this underutilized qualitative research method may be helpful to other researchers and inform future research in health services research.